2015
DOI: 10.1515/helia-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sunflower (Helianthus annuus L.) Hybrids Using Multivariate Statistical Analysis

Abstract: Evaluation and characterization of sunflower hybrids using morphological, physiological and biochemical data are necessary and essential in sunflower breeding programs. The aim of this paper was to evaluate the productive possibilities of some sunflower hybrids grown in Macedonian environmental conditions. The experiment was carried out during the period 2013 and 2014 on the research field of the Faculty of Agriculture, “Goce Delchev” University – Shtip, in Ovche Pole locality, Republic of Macedonia. Total 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Analyzing genetic diversity through multivariate statistics involved the use of cluster analysis, and principal component analysis for grouping genotypes based on the similarities and differences among them (Peeters and Martinelli, 1989 ; Nasreen et al, 2011 ). According to Mohammadi and Prasanna ( 2003 ), many researchers have previously successfully utilized these multivariate techniques for diversity analysis in different crops such as barley (Ruzdik et al, 2015 ), wheat (Cross, 1992 ), sorghum (Hailu et al, 2006 ), and sunflower (Ayana and Bekele, 1999 ). Results of cluster analysis grouped CMS and restorer lines separately.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing genetic diversity through multivariate statistics involved the use of cluster analysis, and principal component analysis for grouping genotypes based on the similarities and differences among them (Peeters and Martinelli, 1989 ; Nasreen et al, 2011 ). According to Mohammadi and Prasanna ( 2003 ), many researchers have previously successfully utilized these multivariate techniques for diversity analysis in different crops such as barley (Ruzdik et al, 2015 ), wheat (Cross, 1992 ), sorghum (Hailu et al, 2006 ), and sunflower (Ayana and Bekele, 1999 ). Results of cluster analysis grouped CMS and restorer lines separately.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster analysis has been used for evaluation of genetic diversity in many crops such as Cornus mas L. (Jaćimović et al, 2015), Helianthus annuus L. (Ruzdik et al, 2015), Aronia mitschurinii A. K. Skvortsov & Maitul. (Vinogradova et al, 2017), Ziziphus jujuba Mill.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Ruždik et al (2015), based on agronomic parameters, had classified 20 sunflower varieties into four groups in their study in Republic of Macedonia. Classifying thirteen sunflower genotypes in Libya by UPGMA procedure, on morphological basis, Mahmoud et al (2012) had found two major groups.…”
Section: Similaritiesmentioning
confidence: 99%